2000
DOI: 10.3354/meps198009
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and macrodiversity in rbcL sequences in ambient phytoplankton populations from the southeastern Gulf of Mexico

Abstract: Ribulose-l,5-diphosphate carboxylase/oxygenase (RuBisCO) large subunit genes (rbcL) were obtained by amplification and cloning of 554 or 614 bp sequences of indigenous phytoplankton populations at 2 stations in the southeastern Gulf of Mexico. One station (Stn 4) was located in a low saiinity, high chlorophyii plume (the 'Green River') which has previously been shown to contain elevated levels of Form IA rbcL mRNA while the other (Stn 7) was in oligotrophic, oceanic water. A diversity of rbcL sequences was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 35 publications
2
56
0
Order By: Relevance
“…Recent studies have shown the importance of pelagophyte subsurface populations , in some cases accounting for as much as 40% of the total picoeukaryote populations at depth. Besides pelagophytes, prasinophytes belonging to Micro monas and Bathycoccus have also been found to be an important member of picoeukaryote populations at CFM depths and deeper waters of the Gulf of Mexico (Paul et al 2000, Hernandez-Becerril et al 2012. Our results are also consistent with Steinberg et al (2001) and Claustre & Marty (1995), who found the above phytoplankton groups to be a significant part of the community in the chlorophyll maximum and deep populations in the subtropical and tropical North Atlantic.…”
Section: Cfm and Deep Watersupporting
confidence: 81%
“…Recent studies have shown the importance of pelagophyte subsurface populations , in some cases accounting for as much as 40% of the total picoeukaryote populations at depth. Besides pelagophytes, prasinophytes belonging to Micro monas and Bathycoccus have also been found to be an important member of picoeukaryote populations at CFM depths and deeper waters of the Gulf of Mexico (Paul et al 2000, Hernandez-Becerril et al 2012. Our results are also consistent with Steinberg et al (2001) and Claustre & Marty (1995), who found the above phytoplankton groups to be a significant part of the community in the chlorophyll maximum and deep populations in the subtropical and tropical North Atlantic.…”
Section: Cfm and Deep Watersupporting
confidence: 81%
“…Picoeukaryotes (including diatoms and pelagophytes) are found throughout the photic zone and numerically dominate the phytoplankton community at the SCM. The diversity of picoeukaryotes at any particular site in the ocean may be quite large; the population may simultaneously include green algae, coccolithophorids, and a great diversity of haptophytes, such as prymnsiophytes, pelagophytes, eustigmatophytes, and diatoms (18,20;Wawrik et al,unpublished). Little is known, however, about the numerical contributions of these groups to oceanic picoplankton communities, nor is there information concerning the relative contributions of these different organisms to primary productivity.…”
Section: Discussionmentioning
confidence: 99%
“…The genes encoding the small and large subunits are designated rbcS and rbcL, respectively (in proteobacteria they are designated cbbS and cbbL, respectively). Phylogenetic analysis revealed that there are four distinct evolutionary lineages within the form I clade of rbcL sequences (20,32). Form IA is found in most marine picocyanobacteria in the genus Prochlorococcus, as well as some Synechococcus species, while it appears that all green algae and other cyanobacteria contain a form IB rbcL.…”
mentioning
confidence: 99%
“…DNA sequences were translated into amino acids and translations were aligned with a representative sample of rbcL sequences obtained from GenBank as were all sequences we recovered previously from similar environments (Paul et al 2000, Wawrik et al 2003. Alignment was performed using Omiga 1.1 (Oxford Molecular Group) using a Clustal W pairwise-weighted alignment method.…”
Section: Methodsmentioning
confidence: 99%